The Influence of Lifestyle and Halal Labels on Purchase Decisions of Packaged Imported Food Products (Case Study of Madrasah Aliyah Matholi'ul Anwar Lamongan Students) - Nabela Eka Nafiq; Syuhada' Syuhada' (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Food is an essential human need. A person is given complete freedom to consume whatever they need. But in deciding a purchase, a person is not allowed to consume food that is not halal (haram). The increase in packaged imported food circulating in Indonesia is feared to cause consumers to buy packaged imported food not based on the halal label but only to meet lifestyle needs. This study aims to determine the influence of lifestyle and halal brands on purchasing decisions of imported packaged food products partially and simultaneously in Madrasah Aliyah Matholi'ul Anwar Lamongan students. The method used in this study is a quantitative method with descriptive analysis and multiple linear regression analysis. The instruments used in this study were primary and secondary data obtained from the research location for testing the device using the validity, reliability, classic assumption, and hypothesis tests. The results showed an influence between lifestyle variables and halal label variables on the decision to purchase packaged imported food products for Madrasah Aliyah Matholi'ul Anwar Lamongan students. So, the results of the T-test (partial), lifestyle gets a value of (8.227), and the halal label variable receives a matter of (3.729). Meanwhile, from the F test (simultaneous), both variables get a discount of (46.730), which is greater than the F table (4.85).